2012
DOI: 10.1155/2012/257172
|View full text |Cite
|
Sign up to set email alerts
|

Brief Group Intervention Using Emotional Freedom Techniques for Depression in College Students: A Randomized Controlled Trial

Abstract: Two hundred thirty-eight first-year college students were assessed using the Beck Depression Inventory (BDI). Thirty students meeting the BDI criteria for moderate to severe depression were randomly assigned to either a treatment or control group. The treatment group received four 90-minute group sessions of EFT (Emotional Freedom Techniques), a novel treatment that combines exposure, cognitive reprocessing, and somatic stimulation. The control group received no treatment. Posttests were conducted 3 weeks late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 34 publications
3
46
0
6
Order By: Relevance
“…This study did not inquire whether students were still using EFT in their daily lives, but found that several students reported on EFT as a useful skill that they learned to reduce their stress levels. This relates to a study conducted by Church, de Asis and Brooks (2012), with 38 college students dealing with depression. After EFT the students were significantly less depressed in comparison to a control group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not inquire whether students were still using EFT in their daily lives, but found that several students reported on EFT as a useful skill that they learned to reduce their stress levels. This relates to a study conducted by Church, de Asis and Brooks (2012), with 38 college students dealing with depression. After EFT the students were significantly less depressed in comparison to a control group .…”
Section: Discussionmentioning
confidence: 99%
“…This sentence, can be altered according to the stressor and will be repeated while doing several tapping rounds, until the emotional response level is reduced to zero. It has been used in several settings (among others for phobia's, depression and stress reduction) and shows promising results, particularly because it is a cost-effective therapy approach (Church, Yount, & Brooks, 2012;Church, de Asis, & Brooks, 2012;Brattberg, 2008;Bougea et al, 2013). A variation of EFT was used which involves tapping on the karate-chop pressure point and saying the sentence three times, and then putting the palms one over the other at the centre of the chest-just below the collar bone-and taking seven deep breaths (CHII, 2008).…”
Section: Case Description: a University-based Stress Management Progrmentioning
confidence: 99%
“…The findings were that the being Science Publications CRP activated by fear, brain frequencies were found to normalise after treatment (Church et al, 2012).…”
Section: Crpmentioning
confidence: 97%
“…The practise of Clinical EFT appears to have physiological effects, with one randomised trial measuring cortisol levels related to depression and anxiety, before and after one of three treatment modalities: Clinical EFT, psychotherapy, or relaxation (Church et al, 2012). The findings were that the being Science Publications CRP activated by fear, brain frequencies were found to normalise after treatment (Church et al, 2012).…”
Section: Crpmentioning
confidence: 99%
See 1 more Smart Citation